2011
DOI: 10.1007/s12094-011-0684-z
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year experience in the management of squamous cell anal canal carcinoma with interstitial brachytherapy

Abstract: Interstitial brachytherapy appears to be an effective and well tolerated treatment for anal carcinoma offering both high local tumour control and anal sphincter preservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Squamous cell anal cancer is a rare tumour which represents 1.5% of gastrointestinal cancers, but in Slovenia only 0.5%. 1 – 5 Despite its infrequent occurrence its incidence is increasing. 4 Women are more commonly affected than men.…”
Section: Introductionmentioning
confidence: 99%
“…Squamous cell anal cancer is a rare tumour which represents 1.5% of gastrointestinal cancers, but in Slovenia only 0.5%. 1 – 5 Despite its infrequent occurrence its incidence is increasing. 4 Women are more commonly affected than men.…”
Section: Introductionmentioning
confidence: 99%
“…A historical clinical study published by Papillon et al [ 9 ] focusing on LDR brachytherapy showed a 69.2% OS rate at 3 years. More recent PDR studies from Gerard et al [ 20 ] and Bruna et al [ 21 ] found respectively an OS rate of 100% at 1 year and 90% at 2 years. Lòpez Guerrera et al [ 22 ] presented a mixed study of LDR and PDR brachytherapy with a 2-year OS rate of 87%.…”
Section: Discussionmentioning
confidence: 99%
“…It arises most commonly from the squamous epithelium in the distal half of the anal canal, with a minority originating from the transitional zone mucosa [6]. Although it currently comprises only approximately 4% of gastrointestinal tract malignancies, the incidence is slowly increasing; current data shows the incidence to be 0.7 per 100,000 per year [1, 2, 6, 7]. The exact reason for this increase is unknown, but hypotheses include increases in the number of patients taking immune-suppressing medications for organ transplants or other disorders, and an increase in immune-suppressing diseases such as HIV/AIDS [1].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of anal carcinomas are squamous cell carcinomas (SCCs) for which the treatment has been well-established and the prognosis is usually favorable [2]. The rate of metastatic disease is low and is typical to either the liver or the lungs.…”
Section: Introductionmentioning
confidence: 99%